2014
DOI: 10.1038/nphys3145
|View full text |Cite
|
Sign up to set email alerts
|

Wettability-independent bouncing on flat surfaces mediated by thin air films

Abstract: The impingement of drops onto solid surfaces 1,2 plays a crucial role in a variety of processes, including inkjet printing, fog harvesting, anti-icing, dropwise condensation and spray coating 3-6. Recent e orts in understanding and controlling drop impact behaviour focused on superhydrophobic surfaces with specific surface structures enabling drop bouncing with reduced contact time 7,8. Here, we report a di erent universal bouncing mechanism that occurs on both wetting and non-wetting flat surfaces for both hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
218
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(236 citation statements)
references
References 32 publications
15
218
3
Order By: Relevance
“…These include splash [6][7][8][9][10], phase-change-induced surface levitation [11][12][13][14][15], skating on a film of trapped air [16][17][18], and rebounding [19][20][21][22]. Recently [11], it was demonstrated that drops can rebound after impact on an extremely cold solid carbon dioxide surface (at -79°C, well below the limit of even homogeneous nucleation of water), because of the formation of a sublimated vapor layer acting both as impact cushion and thermal insulator, enabling drops to hover and rebound without freezing.…”
Section: Introductionmentioning
confidence: 99%
“…These include splash [6][7][8][9][10], phase-change-induced surface levitation [11][12][13][14][15], skating on a film of trapped air [16][17][18], and rebounding [19][20][21][22]. Recently [11], it was demonstrated that drops can rebound after impact on an extremely cold solid carbon dioxide surface (at -79°C, well below the limit of even homogeneous nucleation of water), because of the formation of a sublimated vapor layer acting both as impact cushion and thermal insulator, enabling drops to hover and rebound without freezing.…”
Section: Introductionmentioning
confidence: 99%
“…However, this interaction is highly complex: Below the drop air is trapped at both the impact center and the expanding front (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and above it the atmosphere constantly interacts with its top surface. As a result, even the very basic question of which part of air plays the essential role is completely unknown.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] There has been considerable focus on understanding their wettability 6,7 and developing them for a wide range of applications including droplet impact resistance, [8][9][10][11][12][13] anti-icing, [14][15][16][17][18][19] dropwise condensation, [20][21][22][23][24] electro-wetting, 25,26 drag reduction, [27][28][29][30][31][32] evaporation, 33,34 and anti-corrosion. [35][36][37][38] An important challenge for broad applicability of these hydrophobic materials is their limited robustness.…”
mentioning
confidence: 99%